Biological nutrient removal by halophilic aerobic granular sludge under hypersaline seawater conditions. (December 2020) - Sarvajith, M.; Nancharaiah, Y.V.
Graphical abstract: Highlights: Halophilic granular sludge was cultivated from autochthonous seawater-born microbes. Biological N and P removals were unaffected at 3.4 to 12% salt concentrations. Efficient ammonium removal via nitritation-denitritation pathway at 3.4 to 12% salt. Effective bio-P removal via EBPR pathway at 3.4 to 12% salt concentrations. Stappia was the dominant genus in halophilic aerobic granular sludge at 12% salt. Abstract: Biological nutrient removal and physical properties of halophilic aerobic granular sludge (hAGS) cultivated from autochthonous seawater-born microbes were investigated under hypersaline seawater conditions. hAGS achieved stable total nitrogen (TN) and total phosphorus (TP) removals of 96 ± 3% and 95 ± 4%, respectively, from seawater-based wastewater at 3.4% salt. At 4 to 12% salt concentrations, stable TN and TP removals of 82–99% and 95–96%, respectively, were maintained over 4 months under seawater conditions. Ammonium and phosphorus were mainly removed by nitritation-denitritation and enhanced biological phosphorus removal pathways, respectively. Stappiaceae (45%) and Rhodobacteraceae (21%) were the dominant genera in hAGS performing nutrient removal at 12% salt. hAGS contained acid-soluble extracellular polymeric substance as the major structural polymer which increased from 0.43 ± 0.02 g/gTS at 3.4% salt to 0.93 ± 0.03 g/gTS at 12% salt. Cultivation of hAGS from autochthonous wastewater-microbes can be a promising approach for achieving biological nitrogen and phosphorus removals from hypersaline seawater-based wastewaters.